Prehospital Stroke Assessment for Large Vessel Occlusions: A Systematic Review. (4th March 2018) - Krebs, William; Sharkey-Toppen, Travis P.; Cheek, Fern; Cortez, Eric; Larrimore, Ashley; Keseg, David; Panchal, Ashish R.
Abstract: Background and Objective : Stroke is the leading cause of disability in the United States and new evidence shows interventional procedures provide better outcomes for large vessel occlusions (LVO). We performed a systematic review of the literature on prehospital stroke scales used to identify LVOs comparing the scales with analysis of the sensitivity, specificity, and predictive values. The goal was to determine if emergency medical services (EMS) are able to accurately identify LVO in the field. Methods : In this systematic review, multiple databases were searched for articles that addressed our goal. The identified studies were evaluated for their statistical performance of various stroke scales. In addition, we assessed biases that may explain the varying results reported. Results : Eight studies encompassing 6787 patients were included in our systematic review. Of the 8 studies, 6 were retrospective studies, 1 was a prospective cohort, and 1 was a prospective observational study. Sensitivities of the studies ranged from 49% to 91% while specificity of the studies varied from 40% to 94%. Conclusion : At this time, further evaluations must be done in the prehospital setting to determine the ease of use and true sensitivity and specificity of these scales in identifying LVOs.